Building information spaces to guarantee access to knowledge among indigenous populations: the case of Costa Rica - Sánchez Espinoza, Florybeth (2009)
This paper is based on the project CENTRO DE CONOCIMIENTO PARA GRUPOS INDÍGENAS CENTROAMERICANOS (GEIC), coordinated by the Escuela de Bibliotecología, Documentación e Información (EBDI) of the Universidad Nacional de Costa Rica, (UNA), which aims to "propose the construction of information spaces for the indigenous population, from the project KNOWLEDGE CENTRE FOR CENTRAL AMERICAN INDIGENOUS GROUPS and with this paper we intend to present the lessons learned during 2003-2007, years of data collection and analysis, establishment of relationships, coordination of activities and implementation of actions aimed at ensuring compliance with the right of access to information of Costa Rican indigenous populations. The goal was to create a GEIC Awareness Center / Central American Indigenous Ethnic Groups to serve as a hub to consolidate the development of processes to strengthen the theme and the development of the indigenous ethnic groups of Central America. The project began in 2003, but have no permanent staff, the process is interrupted until January 2004, with the development of the first phase, which includes five goals in implementing Costa Rica. In subsequent phases are expected to include other Central American countries. The Costa Rican indigenous population is 63.876 people, representing 1.6% of the population, there are eight different indigenous social groups, Cabecar, Bribris, Ngabe, Terra, Borucas, Huetar, and Malekus Chorotegas, live in 24 territories and speak in 6 languages Indians. They are migratory and indigenous people join the Miskitos of Nicaragua and Panama Ngabe of working in agricultural production in different parts of the country. Project GEIC sought the implementation of the proposed creation of a special intelligence unit in indigenous affairs in Talamanca Shiroles, this diagnosis was made in the area, determining the availability of resources: technological, human, economic and educational. It currently is seeking financing and managing local, national, and international to meet the costs, which is a little difficult by the lack of appreciation of the importance of information in indigenous communities. Another parallel to this activity is to build a web site available at: http://www.una.ac.cr/bibliotecología/proyectogeic, which was endorsed by the indigenous communities, with the participation of actors and. At that time they explained each section of the same and asked them for their observations and comments thereon to engage (as) and feel appropriate (as) the same.